PENGEMBANGAN KOMPLEMENTER PADA IBU NIFAS DENGAN PENDEKATAN TERAPI MENGGUNAKAN DAUN SIRIH DAN DAUN BINAHONG UNTUK MEMPERCEPAT PENYEMBUHAN LUKA - Antri Ariani; Hani Oktafiani; Andria Pragholapati (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
Perineal wound care can be done to avoid delays in the wound, one of which is by using boiled water from binahong leaves or boiled water from red betel leaves which have an antibiotic effect. After being evaluated from survey data, the more effective way to dry perineal wounds is binahong leaves because mothers who use boiled water of binahong have perfectly dry perineal sutures within 4 days while mothers who use boiled water of betel leaves have perfectly dry perineal sutures within 7 days.